The Application of Sustainable Materials in the Design of a Culinary Center at Klayar Beach, Pacitan - Marcelina Dwi Setyowati; Adita Dwi Kusumawati (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
Pacitan has many natural tourist destinations, one of which is Klayar Beach which is the mainstay of the Pacitan Regency Government in increasing regional income. Klayar Beach has experienced an increase in the number of visitors, so it needs supporting facilities that can be used by visitors while on Klayar Beach. It is also hoped that the design of the Culinary Center can improve the economy of the people around the Klayar Beach area. The use of Sustainable Materials was chosen as a solution to problems that respond to environmental conditions at Klayar Beach. The selected sustainable material that is applied to the design is bamboo material which is widely used by people in Pacitan. Bamboo is a sustainable material because it grows faster, is stronger, cheap and easy to get, is flexible, and lasts a long time with a pre-preservation process. The design method with descriptive qualitative includes problem identification, data collection, analysis and concept synthesis. The data collected is in the form of primary and secondary data and then analyzed so that the results obtained will be applied to the synthesis of the design concept. The final results obtained are to get the concept of mass composition, and the concept of building structures that respond to the environment by using bamboo materials as an implementation of the selected sustainable material concept.